2016
DOI: 10.1002/ece3.2021
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic patterns of Merodon hoverflies in the Eastern Mediterranean region: revealing connections and barriers

Abstract: We investigated the phylogeographic patterns of Merodon species (Diptera, Syrphidae) in the Eastern Mediterranean. Ten species were sampled on five different islands and mainland sites as a minimum. All samples were screened for their mtDNA COI barcode haplotype diversity, and for some samples, we additionally generated genomic fingerprints. The recently established zoogeographic distribution categories classify these species as having (1) Balkan distribution; (2) Anatolian distribution; (3) continental areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 70 publications
(117 reference statements)
1
28
0
Order By: Relevance
“…, Ståhls et al. ), and perhaps these resources are affected even at moderate fire severities. Furthermore, their lower abundance may also be associated with increased drought following moderate and higher fire severity (Ponisio et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Ståhls et al. ), and perhaps these resources are affected even at moderate fire severities. Furthermore, their lower abundance may also be associated with increased drought following moderate and higher fire severity (Ponisio et al.…”
Section: Discussionmentioning
confidence: 99%
“…Among hoverflies, the immature stages of the abundant Eumerus spp. group and Merodon avidus species are associated with belowground storage organs of plants (Grkovi c et al 2015, St ahls et al 2016, and perhaps these resources are affected even at moderate fire severities. Furthermore, their lower abundance may also be associated with increased drought following moderate and higher fire severity (Ponisio et al 2016).…”
Section: Response To Fire Severity: Patternmentioning
confidence: 99%
“…The nuclear 28S rRNA gene is also used as an additional source of information to resolve taxonomic uncertainties (Mengual et al., ), although it is usually applied at the genus level. Inter‐simple sequence repeats (ISSR) have been used to discern closely related insect species (Kehlmaier & Assmann, ) and for assessments of population‐level genetic polymorphism (Ståhls et al., ). In addition to molecular data, geometric morphometry has been successfully used in cryptic species delimitation due to its considerable discriminatory and statistical power in revealing minor but stable morphological variation, often undetectable to the naked eye (Nedeljković et al., , ; Šašić et al., ; Vujić, Ståhls, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ståhls et al. () recently studied the phylogeographical patterns of selected Merodon species in the eastern Mediterranean. They concluded that both current and past geographical barriers have influences on the dispersal and evolution of Merodon .…”
Section: Introductionmentioning
confidence: 99%
“…PD has mostly been measured based on phylogenetic trees or cladograms (Faith 1992). This notion can be extended to intra-specific variability, in which case individuals or populations of one or more species are studied under the same framework (Ståhls et al 2016). Yet, in lieu of precise phylogenetic information on the member taxa of a community, taxonomic diversity (LD) may be used as a surrogate for PD, being calculated from an ultrametric tree (i.e.…”
Section: Introductionmentioning
confidence: 99%